Bullying Awareness: Memahami dan Mengidentifikasi Tanda-Tanda Bullying Pada Siswa SMAN 21 Jakarta - Sarovah Widiawati; Novi Indah Susanthi; Irwan Chairuddin (Jurnal Pengabdian Masyarakat dan Penelitian Terapan, 2024)
Bullying is behavior that is deliberately carried out to make the victim feel hurt and uncomfortable. This behavior is carried out with physical or verbal contact. Bullying is usually carried out by perpetrators who are stronger or have more power than the victim. Therefore, there is a need to understand bullying and how to identify signs of bullying, especially at school because this behavior is detrimental to students and can disrupt learning activities at school. Faculty of Management and Business, Trisakti Institute of Transportation and Logistics carries out Community Service (PKM) at SMAN 21 Jakarta. The PKM was carried out on 31 grade 10 high school students and 3 teams of lecturers from ITL Trisakti. The implementation of PKM activities is carried out in the form of socialization, starting with questions and answers about bullying and also asking students to fill out a questionnaire via G-Form to find out students' knowledge regarding bullying and types of bullying behavior. After that, the author gave a presentation and asked questions regarding their experiences with bullying behavior. Finally, the author gave the questionnaire again to determine the increase in their knowledge and also their experiences with bullying behavior to find out comprehensive information from students. Through socialization regarding bullying behavior, it can be seen that around 75% of students at SMAN 21 Jakarta are able to understand and identify bullying behavior. 25% of them have experienced bullying behavior at school or outside school. The bullying was carried out by classmates and friends of students from other schools. The types of bullying experienced by these students were verbal bullying, 65% through ridicule and ridicule, 30% mental/psychological bullying through exclusion, and 5% cyberbullying.